High‐Performance Full‐Photolithographic Top‐Contact Conformable Organic Transistors for Soft Electronics - Zhao, Xiaoli (Adv Sci (Weinh), 2021)
Organic thin‐film transistors (OTFTs) are identified to be the most promising candidate for next‐generation wearable and implantable electronics because of their unique advantages including their flexibility, low cost, long‐term biocompatibility, and simple packaging. However, commercialization of organic transistors remains an enormous challenge due to their low mobility and lack of scalable strategy for high‐precise soft devices. Here, a novel photolithography fabrication strategy is proposed, which is completely compatible with various commercial organic semiconductor materials, for the first demonstration of the fully photolithographic top‐contact conformable OTFTs with the device density as high as 1523 transistors cm(−2). Excellent electrical and mechanical properties with device yield as high as 100%, field‐effect mobility up to 1–2 cm(2) V(−1) s(−1), and outstanding conformability are shown. This work provides a new strategy that can fully maximize the advantages of organic materials and photolithography technology, showing a great prospect in the development of high‐performance, high‐precise organic devices toward the commercialized and industrialized soft electronic products.